Autoimmune Encephalitides and Rapidly Progressive Dementias - Wesley, Sarah F.; Ferguson, Damien (Seminars in Neurology, 2019)
Rapidly progressive dementia (RPD) or cognitive decline is a common presenting complaint in neurology. While primary dementia is often a concern, other forms of reversible dementia must be thoroughly considered. This article focuses on the growing field of autoimmune encephalitis (AE) as it pertains to the differential diagnostic considerations in a work-up for RPD. Understanding clues in the history and examination is the first step in identifying patients with a potential autoimmune cause for RPD. While testing for infectious and toxic-metabolic etiologies is commonly preformed, it is necessary to consider early ancillary testing for AE in appropriate cases of RPD. Autoantibody testing in the spinal fluid and serum, brain imaging, and electroencephalography all form the first line of investigations for AE. Treatment options and strategies depend on the AE subtype and a number of individual patient considerations.
Keywords: autoimmune encephalitis; rapidly progressive dementia; autoimmune dementia